IMPLEMENTASI DANA BANTUAN OPERASIONAL SEKOLAH (BOS) DALAM PENYELENGGARAAN PENDIDIKAN SEKOLAH DASAR KECAMATAN TEBING TINGGI BARAT KABUPATEN KEPULAUAN MERANTI TAHUN 2015 - Septia Ningsih; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
School Operational Assistance (BOS) is a government program which is basically the provision of funding for non-personnel operating costs for basic education unit, as the executor of compulsory education. Thus the Ministry of Education and Culture issued a regulation the Minister of Education and Culture of the Republic of Indonesia Number 161 of 2014 on Technical Guidelines for Financial Accountability Educational Uses And Fiscal Year 2015. The purpose of this study was to look at the implementation of the School Operational Aid (BOS) in the Implementation of School Education Elementary District of Tebing Tinggi West District Meranti Islands in 2015, especially on the School Operational assistance (BOS) in the Implementation of Primary Education District of Tebing Tinggi West and to determine the factors that affect the implementation fund School Operational assistance (BOS) in the Implementation of Primary Education District of Tebing West high Meranti Islands District 2015, especially on the School Operational assistance (BOS) in the Implementation of the District Primary Education Tebing Tinggi West. In theory the implementation model by Van Meter and Van Horn, there are six variables that establish linkages between policy and performance, namely: standards and policy goals, resources, communication between organizations, implementing characteristics, disposition implementor and environmental conditions of economic, social and political. The method used is descriptive qualitative with purposive sampling technique. Informants in this study is Sasar Superintendent of Education Department of Education and Culture, Primary School Principal, Treasurer Elementary School, and Parents. Based on the research and discussion that researchers do in the field, it was found that the implementation of the School Operational Aid (BOS) in the Implementation of the District Primary Education Tebing Tinggi West Meranti Islands District 2015 has not been implemented to the fullest. That's because the various factors that affect the implementation of this regulation is difficult implemented optimally.